Floristic Composition and Soil Characteristics in Muara Kaman Sedulang Nature Reserve, East Kalimantan - Ulfah , Ulfah Karmila Sari; Bina , Bina Swasta Sitepu; Mukhlisi , Mukhlisi Mukhlisi; Puji, Puji Mulyanto (Jurnal Wasian, 2021)
Muara Kaman Sedulang Nature Reserve in East Kalimantan has been damaged due to anthropogenic activities and natural fires. The study aims to explore the floristic composition and soil characteristics in the rehabilitation and protection block to provide plant species information for the restoration activity. Vegetation data were collected in each block with a purposive random sampling method, in a total of 0,36 ha plot sample in rehabilitation block and 0,32 ha in protection block. Soil characteristics samples for physical and chemical measurement were collected in each plot with a composite technique at the soil surface (0 – 30 cm). There are 15 species recorded in rehabilitation block and 30 species in the protection block. The diameter distribution indicated that there are differences in the regeneration process after periods of destruction on each block. The diversity index in the rehabilitation block is low, while in the protection block is low to middle. Mallotus sumatranus is a dominant species in the rehabilitation block, whereas in the protection block is Lagerstroemia speciosa. Lepisanthes alata always presents in all research plots indicated suitability for all type of habitat in the area. Soil type is Endoaquepts Dystrudepts with silt clay loam texture and acid soil.